A ferret model of COPD-related chronic bronchitis - Raju, S. Vamsee (JCI Insight, 2016)
Chronic obstructive pulmonary disease (COPD) is the third leading cause of death in the US. The majority of COPD patients have symptoms of chronic bronchitis, which lacks specific therapies. A major impediment to therapeutic development has been the absence of animal models that recapitulate key clinical and pathologic features of human disease. Ferrets are well suited for the investigation of the significance of respiratory diseases, given prior data indicating similarities to human airway physiology and submucosal gland distribution. Here, we exposed ferrets to chronic cigarette smoke and found them to approximate complex clinical features of human COPD. Unlike mice, which develop solely emphysema, smoke-exposed ferrets exhibited markedly higher numbers of early-morning spontaneous coughs and sporadic infectious exacerbations as well as a higher level of airway obstruction accompanied by goblet cell metaplasia/hyperplasia and increased mucus expression in small airways, indicative of chronic bronchitis and bronchiolitis. Overall, we demonstrate the first COPD animal model exhibiting clinical and pathologic features of chronic bronchitis to our knowledge, providing a key advance that will greatly facilitate the preclinical development of novel treatments for this disease.